Resenha: FREITAS FILHO, Armando. Raro mar. São Paulo: Companhia das Letras, 2006. (Revista do Centro de Estudos Portugueses, 2006)
Resenha: FREITAS FILHO, Armando. Raro mar. São Paulo: Companhia das Letras, 2006.